Gender Portrayal in Outdoor Advertising in Punjab and Khyber Pakhtunkhwa (KPK) Provinces of Pakistan - Rana, Faiz Ullah (Journal of Peace, Development and Communication, 2021)
Abstract Gender portrayal and the representations of males and females in advertising remains the core interest of researchers from gender studies and communication research. In advertising scholarship, it is often found that there are differences in gender portrayal specifically due to the cultural contexts. In the present study, we explore the gender portrayal in outdoor billboard advertising of two provinces of Pakistan; Punjab and KPK. Theoretically and conceptually, the study takes roots from cultural studies on advertising and social semiotics studies on gender and advertising. We collect data of 360 billboard advertisements from two cities of Punjab and two cities of KPK. We coded 654 units in these 360 billboards according to the conceptual categories of social semiotics. In the present study we found that female models are portrayed more as compare to the male models in outdoor advertising of both provinces; Punjab and KPK. Although, the dominant pattern of gender portrayal in advertisements of KPK is similar to Punjab, however, it is slightly different from Punjab. In KPK, males are also portrayed as submissive. Females are more associated with nurturing roles as compared to Punjab. Hence, it is concluded that in outdoor advertising of Pakistan, females are objectified and they are mostly used for their glamour and beauty. On the contrary, males are portrayed as dominant and in power.